A GIS-based agroecological model for sustainable agricultural production in arid and semi-arid areas: The case of Kerman Province, Iran - Kamaleddin Aghaloo; Ayyoob Sharifi (Current Research in Environmental Sustainability, 2023)
Promoting the adoption of crop species with medicinal and commercial value can provide new opportunities for local communities to export their products. Meanwhile, using sustainable water resources and minimizing the over-exploitation of groundwater are urgently needed due to the critical status of aquifers in many parts of the world. Most existing studies are focused on a single aspect of this issue. However, few studies have incorporated the results of several suitability models in agroecological processes. Rossa Damascena Mill is recognized as a crop species and raw material with added value and considerable profitability. In addition, it is resistant to drought and adapts to different climatic conditions. This paper presents a framework for the optimal detection of suitable land for agroecological activities. We tested the framework in Kerman Province (Iran) to identify: 1) suitable lands for Rossa Damascena Mill cultivation, 2) suitable lands for agricultural rainwater harvesting (ARWH) systems, and 3) suitable lands for developing both Rosa farms and RWH simultaneously. Results revealed that approximately 24,808.5 km2 of land (14% of the province's land) is suitable for dry farming. Also, RWH systems can be implemented in 19,024.4 km2 of land (11% of the province). Overlapping land suitability for rainfed agriculture and RWH systems highlights that only 4% of the study area can be cultivated. Finally, two strategies are suggested: developing Rosa Damascena cultivation in a) ranked areas for rainfed agriculture and b) farms/gardens that can be supplied by RWH systems nearby. Sensitivity analysis and overall accuracy assessment validated the results and robustness of the modeling. This proposed model can be helpful for making effective decisions regarding the region's sustainable development to strengthen the local economy and address water stress issues, especially in arid and semi-arid areas. The results have implications for different SDGs, including SDG 12 on sustainable consumption and production and SDG 15 on life on land. They can also be used to enhance resilience against stressors induced by climate change.